The Influence of Perceived Organizational Support, Employee Enggagement and Work Motivation on Employee Performance - Abdur Rosid; Laily Muzdalifah; Nafia Ilhama Qurratu’aini (GREENOMIKA, 2023)
Perceived organizational support is known that employees feel lacking in the perception of organizational support provided by the company to employees. Employee engagement with rapid technological changes and a very dynamic environment in every aspect of human life. The purpose of this research is to determine the effect of perceived organizational support on employee performance, employee engagement on employee performance, Work Motivation on employee performance. This research uses a correlation research design. The sample for this research consisted of 40 respondents using a saturated sampling method. The statistical tool used is SPSS. The research results show that perceived organizational support does not significant effect on employee performance. Employee engagement and work motivation have a significant effect on employee performance.